KONSEP DIRI PADA PELAKU PERCOBAAN BUNUH DIRI PRIA USIA DEWASA MUDA DI BALI - AA Sagung Weni Kumala Ratih; David Hizkia Tobing (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2017)
In these past years, the phenomenon’s of suicide case are becomes worrying. Indonesia, as one of a country who has a collective culture has a quite high number of suicide case. WHO estimates that by year 2020 the number of suicide case in Indonesia will be increased up to 2.4 percent from 100.000 people, if the government and the society don’t take it as serious things to concern (Mardani, 2012). Bali province as one of the province in Indonesia has a high rate in case of suicide, besides the Special Region of Yogyakarta (Hawari, 2010). Suicide cases in Bali are majority done by man, young adult people (Lesmana, 2008). Suicide and the attempted suicide are one of the ways or act to hurt or harm themselves, which arise as one of the effect of an intrapsychic conflict within themselves. One of the factors that is influence the occurring of a behavior including the suicide behavior and the attempted suicide are the self-concept. The self-concept is a way of someone to see themselves, the perception about the social environment (the other people), and also the perception about the way people think and see about themselves. This phenomenon becomes an interesting thing by the researcher to know what self-concept that is owned by the man young adult person suicide attempters in Bali. This study use qualitative method and phenomenological approach, with 5 (five) man young adult suicide attempters in Bali. This study shows that there are 5 (five) component of self-concept that is occurs in the man young adult in Bali, however this component self-concept are not totally positive. Eventhough there are self-components that is shows the positive things of a self-acceptance and self-evaluation, but, almost of this shows the negative side of the self-concept characteristic, especially the social self component and the personal self component that is owned by the respondents. Some factors that is influence the self-concept of the man young adult suicide attempters in Bali are, the education, the economic, genetic, social learning, and culture. Keywords : Self-Concept, Attempted Suicide, Young Adult, Bali